2019
DOI: 10.1186/s13054-019-2472-z
|View full text |Cite
|
Sign up to set email alerts
|

Trying to identify who may benefit most from future vitamin D intervention trials: a post hoc analysis from the VITDAL-ICU study excluding the early deaths

Abstract: Background Vitamin D supplementation has shown promise for reducing mortality in the intensive care setting. As a steroid prohormone with pleiotropic effects, there may be a lag between administration and observing clinical benefit. This secondary analysis of the VITdAL-ICU study sought to explore whether the effect size of vitamin D on mortality was different when study participants who died or were discharged early were excluded. Methods The VITdAL-ICU study was a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 60 publications
(52 reference statements)
3
46
0
1
Order By: Relevance
“…Similarly, critically ill patients have a very high prevalence of vitamin D deficiency, and low vitamin D levels are clearly associated with greater illness severity, morbidity, and mortality in both adult and pediatric intensive care unit (ICU) patients, as well as medical and surgical ICUs [23]. However, as in most other populations, the most important question remains unanswered: whether low vitamin D is an innocent bystander, simply reflecting greater disease severity, or represents an independent and modifiable risk factor amenable to rapid normalization through loading dose supplementation [24,25].…”
Section: Vitamin D Deficiency In Critical Illnessmentioning
confidence: 99%
“…Similarly, critically ill patients have a very high prevalence of vitamin D deficiency, and low vitamin D levels are clearly associated with greater illness severity, morbidity, and mortality in both adult and pediatric intensive care unit (ICU) patients, as well as medical and surgical ICUs [23]. However, as in most other populations, the most important question remains unanswered: whether low vitamin D is an innocent bystander, simply reflecting greater disease severity, or represents an independent and modifiable risk factor amenable to rapid normalization through loading dose supplementation [24,25].…”
Section: Vitamin D Deficiency In Critical Illnessmentioning
confidence: 99%
“…Several large studies and meta-analyses have found that vitamin D deficiency is associated with greater illness severity, morbidity and mortality in both critically ill adult and geriatric patients, but there is a lack of clinical data demonstrating the efficacy of normalising levels as an effective therapy and trials are being designed to this end [53].…”
Section: Sars-cov-2 and Covid-19mentioning
confidence: 99%
“…5 Early finding of vitamin D deficiency and supplement can decrease the risk of many diseases and mortality rate. 6 Free Full Text Articles are Available at www.jnma.com.np Level of vitamin D is tested by quantitative method, chemiluminescent immunoassay (CLIA) methods. Blood sample (5 mL) was taken in gel tube for each subject and serum was separated by centrifuge to estimate vitamin D [25(OH)D].…”
Section: Introductionmentioning
confidence: 99%